Chapter 2
Chapter 2
Chapter 2
Matrices
Chapter 2 Matrices
Section 2.1
Introduction to Matrices
Matrices (Definition 2.1.1)
(1, 2)-entry
1 2 4 is a 1 × 1 matrix.
3 4 is a 3 × 2 matrix.
A 1 × 1 matrix is usually
0 −1 treated as a number in
(3, 1)-entry computation.
2 1 0 is a 1 × 3 matrix. 1
1 is a 3 × 1 matrix.
2 3.1 −2 2
1
3 2
0 is a 3 × 3 matrix.
0 π 0
(Definition 2.1.3
Column and row matrices & Example 2.1.4)
1
1 is a column matrix.
2
2 1 0 is a row matrix.
2 3 4
Then A = .
3 4 5
1 if i + j is even
Let B = (bi j )3 × 2 where bi j =
−1 if i + j is odd.
1 −1
Then B = −1 1 .
1 −1
Square matrices (Definition 2.1.7.1 & Example 2.1.8.1)
non-diagonal
entries
Diagonal matrices (Definition 2.1.7.2 & Example 2.1.8.2)
2 0 0 0
1 0 0
0 0 0 3 0 0
4 0 3 0
0 2 0 0 0 0
0 0 2
0 0 0 1
Scalar matrices (Definition 2.1.7.3 & Example 2.1.8.3)
2 1 6 −2
1 −1 0
0 4 1 3 0 −1
4 −1 3 2
4 2 6 0 0 0
0 2 2
−2 −1 0 1
Triangular matrices (Definition 2.1.7.7 & Example 2.1.8.7)
Section 2.2
Matrix Operations
Equal (Definition 2.2.1 & Example 2.2.2)
1 x 1 −1 1 −1 0
Let A = , B= and C = .
2 4 2 4 2 4 0
Then A = B if and only if x = −1;
B≠C
and A ≠ C for any values of x.
Matrix addition (Definition 2.2.3.1)
2 3 4 1 2 3
Let A = , and B = .
4 5 6 −1 −1 −1
2+1 3+2 4+3
Then A + B =
4 + (−1) 5 + (−1) 6 + (−1)
3 5 7
= .
3 4 5
Matrix subtraction (Definition 2.2.3.2)
2 3 4 1 2 3
Let A = , and B = .
4 5 6 −1 −1 −1
2−1 3−2 4−3
Then A − B =
4 − (−1) 5 − (−1) 6 − (−1)
1 1 1
= .
5 6 7
Scalar multiplication (Definition 2.2.3.3)
2 3 4
Let A = .
4 5 6
4·2 4·3 4·4
Then 4A =
4·4 4·5 4·6
8 12 16
= .
16 20 24
Some remarks (Remark 2.2.5)
To prove A + (B + C) = (A + B) + C:
Recall that two matrices are equal if
(i) they have the same size and
(ii) their corresponding entries are equal.
(Remark 2.2.10.1)
We can only compute the product AB when the
number of columns of A is equal to the number of rows
of B.
Examples (Example 2.2.9.1)
1 1
1 2 3
2 3
4 5 6
−1 −2
1 · 1 + 2 · 2 + 3 · (−1)
=
2
= .
Examples (Example 2.2.9.1)
1 1
1 2 3
2 3
4 5 6
−1 −2
1 · 1 + 2 · 2 + 3 · (−1) 1 · 1 + 2 · 3 + 3 · (−2)
=
2 1
= .
Examples (Example 2.2.9.1)
1 1
1 2 3
2 3
4 5 6
−1 −2
1 · 1 + 2 · 2 + 3 · (−1) 1 · 1 + 2 · 3 + 3 · (−2)
=
4 · 1 + 5 · 2 + 6 · (−1)
2 1
= .
8
Examples (Example 2.2.9.1)
1 1
1 2 3
2 3
4 5 6
−1 −2
1 · 1 + 2 · 2 + 3 · (−1) 1 · 1 + 2 · 3 + 3 · (−2)
=
4 · 1 + 5 · 2 + 6 · (−1) 4 · 1 + 5 · 3 + 6 · (−2)
2 1
= .
8 7
Examples (Example 2.2.9.2)
1 1
1 2 3
2 3
4 5 6
−1 −2
5 7 9
= 14 19 24
−9 −12 −15
Multiplication isn’t commutative (Remark 2.2.10.2)
−1 0 1 2
For example, let A = and B = .
2 3 3 0
−1 −2 3 6
Then AB = and BA = .
11 4 −3 0
Hence AB ≠ BA.
Multiplication isn’t commutative (Remark 2.2.10.3)
0 1 1 1
For example, let A = and B = .
0 1 0 0
We have A ≠ 0, B ≠ 0 and
0 1 1 1 0 0
AB = = = 0.
0 1 0 0 0 0
Some basic properties (Theorem 2.2.11)
1 2
For example, let A = .
1 3
1 2 1 2 1 2 11 30
Then A3 = = .
1 3 1 3 1 3 15 41
Powers of square matrices (Remark 2.2.14)
a1
a2
A= where ai = ai 1 ai 2 ··· ai p
⁞
am is the i th row of A.
b1 j
b2 j
where bj = is the j th column of B.
⁞
bp j
Some useful notation (Notation 2.2.15)
b1 j
b2 j The i th row of A
where ai bj = ai 1 ai 2 ··· ai p pre-multiply to
⁞ the j th column of B.
bp j
The i th row of AB is
ai1b11 + ai2b21 + ··· + aipbp1 ai1b12 + ai2b22 + ··· + aipbp2 ··· ai1b1n + ai2b2n + ··· + aipbpn
1 2 3
Let A = with a1 = 1 2 3 and a2 = 4 5 6 ;
4 5 6
1 1 1 1
B= 2 3 with b1 = 2 and b2 = 3 .
−1 −2 −1 −2
a1
Then A = , B= b1 b2 and
a2
a1b1 a1b2 a1B 2 1
AB = = Ab1 Ab2 = = .
a2b1 a2b2 a2B 8 7
Linear systems (Remark 2.2.17)
x1 b1
x2 b2
Let A = (ai j )m × n, x = and b = .
⁞ ⁞ b is called the
xn bm constant matrix.
4 5 6 x 5
can be written as 1 −1 0 y = 2
0 1 −1 z 3
4 5 6 5
or x 1 + y −1 +z 0 = 2 .
0 1 −1 3
Solutions to linear systems
4 5 6 3 5
because 1 −1 0 1 = 2 .
0 1 −1 −2 3
(Definition 2.2.19 & Example 2.2.20
Transposes & Remark 2.2.21.1)
1 5
1 2 3 4 2 6
Let A = . Then A =
T .
5 6 7 8 3 7
4 8
Let A be an m × n matrix.
1. (AT)T = A.
2. If B be an m × n matrix, then (A + B)T = AT + BT.
3. If c is a scalar, then (cA)T = cAT.
4. If B be an n × p matrix, then (AB)T = BTAT.
Proof of (AB)T = BTAT (Theorem 2.2.22.4)
Section 2.3
Inverses of Square Matrices
Inverses (Discussion 2.3.1)
2 −5 3 5
Let A = and B = .
−1 3 1 2
Then
2 −5 3 5 1 0
AB = = = I,
−1 3 1 2 0 1
3 5 2 −5 1 0
BA = = = I.
1 2 −1 3 0 1
2 −5 4
X=
−1 3 0
3 5 2 −5 3 5 4
⇒ X=
1 2 −1 3 1 2 0
12
⇒ IX =
4
12
⇒ X=
4
By Theorem 2.2.11.3, I X = X.
Examples (Example 2.3.3.3)
In next section, we
shall learn a
systematic method
to check whether a
1 0
Show that A = is singular. square matrix is
1 0 invertible.
(Proof by contradiction)
a b
Assume the contrary, i.e. A has an inverse B = ,
c d
1 0
i.e. BA = I = .
0 1
a b 1 0 a+b 0
On the other hand, BA = = .
c d 1 0 c+d 0
It is impossible.
Hence our assumption is wrong, i.e. A is singular.
Cancellation laws (Remark 2.3.4)
So AB = I ⇒ CAB = CI ⇒ I B = C ⇒ B = C.
(Notation 2.3.6)
a b
Let A = . If ad − bc ≠ 0, then A is invertible and
c d
d −b
1 d −b ad − bc ad − bc
A = ad − bc
−1 = −c a
.
−c a
ad − bc ad − bc
d −b
ad − bc ad − bc
Proof: Let B = −c a
.
ad − bc ad − bc (Remark 2.3.7)
To show that A is invertible and B is the inverse of A,
by Definition 2.3.2, we need to check AB = I and BA = I.
(By Theorem 2.4.12 in the next section, we shall see that we only need
to check one of the two conditions: AB = I or BA = I.)
2 x 2 matrices (Example 2.3.8)
d −b ad − bc −ab + ba
a b ad − bc ad − bc 1ad 0− bc ad − bc
AB = −c a
= cd − dc
= I,
−cb + da
c d 0 1
ad − bc ad − bc ad − bc ad − bc
d −b da − bc db − bd
ad − bc ad − bc a b 1ad0− bc ad − bc
BA = −c a
= −ca + ac
= I.−cb + da
c d 0 1
ad − bc ad − bc ad − bc ad − bc
AT(A−1)T = (A−1A)T = I T = I
and similarly (A−1)TAT = (AA−1)T = I T = I.
So AT is invertible and (AT)−1 = (A−1)T.
(Definition 2.3.11
Powers of square matrices & Example 2.3.12)
1 2 3 −2
For example, let A = . Then A−1 = .
1 3 −1 1
3 −2 3 −2 3 −2
So A−3 = (A−1)3 =
−1 1 −1 1 −1 1
41 −30
= .
−15 11
Some basic properties (Remark 2.3.13)
Section 2.4
Elementary Matrices
Some useful terms from Chapter 1 (Definition 2.4.1)
1 0 0
Let E1 = 0 2 0 .
0 0 1
1 0 0 1 0 2 3 1 0 2 3
Then E1A = 0 2 0 2 −1 3 6 = 4 −2 6 12 = B.
0 0 1 1 4 4 0 1 4 4 0
Elementary row operations (Discussion 2.4.2.1)
1
0
1
E= k . i th row
1
0
1
kRi
Then A EA.
Elementary row operations (Discussion 2.4.2.1)
If k ≠ 0, then E is invertible
and thi column
1
1 0
1
E −1 = k
. i th row
1
0
1
1
k Ri
Note that A E −1A.
Elementary row operations (Discussion 2.4.2.2)
1 0 0
Let E2 = 0 0 1 .
0 1 0
1 0 0 1 0 2 3 1 0 2 3
Then E2A = 0 0 1 2 −1 3 6 = 1 4 4 0 = B.
0 1 0 1 4 4 0 2 −1 3 6
Elementary row operations (Discussion 2.4.2.2)
1
i th row 0
1
0 1
1
Ri ↔ Rj
E= . Then A EA.
1
1 0 E is invertible and
j th row
1 E−1 = E.
0
1
Elementary row operations (Discussion 2.4.2.3)
1 0 0
Let E3 = 0 1 0 .
2 0 1
1 0 0 1 0 2 3 1 0 2 3
Then E3A = 0 1 0 2 −1 3 6 = 2 −1 3 6 = B.
2 0 1 1 4 4 0 3 4 8 6
Elementary row operations (Discussion 2.4.2.3)
1
0
1
1
E= ;
k 1 j th row
1
0
1
Elementary row operations (Discussion 2.4.2.3)
1
0
1
1 k j th row
E= .
1
1
0
1
Rj + kRi
Then A EA.
Elementary row operations (Discussion 2.4.2.3)
E is invertible
and if i < j, i th column j th column
1
0
1
1
E−1 = ;
−k 1 j th row
1
0
1
Elementary row operations (Discussion 2.4.2.3)
j th column i th column
and if i > j,
1
0
1
1 −k j th row
E−1 = .
1
1
0
1
Rj − kRi
Note that A E−1A.
Elementary matrices (Definition 2.4.3 & Remark 2.4.4)
0 4 2 1 0 2
R1 ↔ R3
A = −2 1 −3 −2 1 −3
E1
1 0 2 0 4 2
0 0 1 0 4 2 1 0 2
E1A = 0 1 0 −2 1 −3 = −2 1 −3
1 0 0 1 0 2 0 4 2
0 0 1
E1 = 0 1 0
1 0 0
An example (Example 2.4.5)
1 0 2 1 0 2
R1 ↔ R3 R2 + 2R1
A −2 1 −3 0 1 1
E1 E2
0 4 2 0 4 2
1 0 0 1 0 2 1 0 2
E2 E1A = 2 1 0 −2 1 −3 = 0 1 1
0 0 1 0 4 2 0 4 2
0 0 1 1 0 0
E1 = 0 1 0 E2 = 2 1 0
1 0 0 0 0 1
An example (Example 2.4.5)
1 0 2 1 0 2
R1 ↔ R3 R2 + 2R1 R3 − 4R2
A 0 1 1 0 1 1
E1 E2 E3
0 4 2 0 0 −2
1 0 0 1 0 2 1 0 2
E3E2E1A = 0 1 0 0 1 1 = 0 1 1
0 −4 1 0 4 2 0 0 −2
0 0 1 1 0 0 1 0 0
E1 = 0 1 0 E2 = 2 1 0 E3 = 0 1 0
1 0 0 0 0 1 0 −4 1
An example (Example 2.4.5)
1 0 2 1
− 2 R3
1 0 2
R1 ↔ R3 R2 + 2R1 R3 − 4R2
A 0 1 1 0 1 1 =B
E1 E2 E3 E4
0 0 −2 0 0 1
1 0 0 1 0 2 1 0 2
E4E3E2E1A = 0 1 0 0 1 1 = 0 1 1
1
0 0 −2 0 0 −2 0 0 1
0 0 1 1 0 0 1 0 0 1 0 0
E1 = 0 1 0 E2 = 2 1 0 E3 = 0 1 0 E4 = 0 1 0
1
1 0 0 0 0 1 0 −4 1 0 0 −2
An example (Example 2.4.5)
0 4 2 1 0 2 0 0 1 1 0 0
A = −2 1 −3 B= 0 1 1 E1 = 0 1 0 E2 = 2 1 0
1 0 2 0 0 1 1 0 0 0 0 1
We have seen that 1 0 0 1 0 0
E4E3E2E1A = B. E3 = 0 1 0 E4 = 0 1 0
1
0 −4 1 0 0 −2
0 0 1 1 0 0
E1−1 = 0 1 0 E2−1 = −2 1 0 Then
1 0 0 0 0 1 A = (E4E3E2E1)−1B
1 0 0 1 0 0 = E1−1E2−1E3−1E4−1B.
E3−1 = 0 1 0 E4−1 = 0 1 0
0 4 1 0 0 −2
System of linear equations (Remark 2.4.6)
⇑
augmented matrix row augmented matrix
(A|b) equivalent (C|d)
System of linear equations (Remark 2.4.6)
If x = u is a solution to Ax = b, then
Au = b ⇒ Ek ··· E2E1Au = Ek ··· E2E1b
⇒ Cu = d
and hence x = u is a solution to Cx = d.
If x = v is a solution to Cx = d, then
Cv = d ⇒ E1−1E2−1 ··· Ek−1Cv = E1−1E2−1 ··· Ek−1d
⇒ Av = b
and hence x = v is a solution to Ax = b.
So we have shown that Ax = b and Cx = d has the
same set of solutions.
Invertible matrices (Theorem 2.4.7)
1 ⇒ 2: If A is invertible, then
Ax = 0 ⇒ A−1Ax = A−10
⇒ Ix = 0
⇒ x = 0.
and hence the system Ax = 0 has only the trivial
solution.
2 ⇒ 3: Suppose the system Ax = 0 has only the trivial
solution.
The augmented matrix of the system is ( A | 0 ).
Invertible matrices (Theorem 2.4.7)
Since Ax = 0 has only the trivial solution, every column of its row echelon
form is a pivot column (see Remark 1.4.8.2).
the number of nonzero rows
⊗ * ··· * 0 = the number of leading entries
Gaussian 0 ⊗ ··· * 0 = the number of pivot columns
(A|0)
Elimination ⁞ ⁞ =n
0 ··· 0 ⊗ 0 Hence there is no zero row.
Suppose the size
of A is n × n. 1 0 ··· 0 0
Gauss-Jordan 0 1 ··· 0 0
=(I|0)
Elimination ⁞ ⁞
0 ··· 0 1 0
Thus the reduced row-echelon form of A is an
identity matrix.
Invertible matrices (Theorem 2.4.7)
1 2 3
Let A = 2 5 3 .
1 0 8
1 2 3 1 0 0 1 0 0 −40 16 9
Gauss-Jordan
2 5 3 0 1 0 0 1 0 13 −5 −3
Elimination
1 0 8 0 0 1 0 0 1 5 −2 −1
−40 16 9
So A−1 = 13 −5 −3 .
5 −2 −1
To check whether invertible (Remark 2.4.10)
1. 1 2 0 1 2 0
Gaussian
A= 2 4 4 0 0 4
Elimination
3 6 3 0 0 0
So A is singular.
a b
2. Let A = .
c d
We already know that if ad − bc ≠ 0, then A is
invertible (see Example 2.3.8).
Actually, A is invertible if and only if ad − bc ≠ 0.
(By using Remark 2.4.10, we can show that if A is invertible,
then ad − bc ≠ 0. Read our textbook for the detailed proof.)
Invertible matrices (Theorem 2.4.12)
Since B is invertible,
AB = I ⇒ ABB−1 = I B−1 ⇒ AI = B−1 ⇒ A = B−1.
Then (by Theorem 2.3.9.3) A is invertible
and A−1 = (B−1)−1 = B.
Finally, BA = BB−1 = I.
An example (Example 2.4.13)
How is A related to AE ?
Answer: AE can be obtained from A by doing an
“elementary column operation”.
(Read our textbook for more details.)
Chapter 2 Matrices
Section 2.5
Determinants
Invertible matrices (Discussion 2.5.1)
a b
Let A = .
c d
Then M11 = d ,
A11 = (−1)1 + 1 det(M11) = d
2 × 2 matrices (Example 2.5.4.1)
a b
Let A = .
c d
a b
Let A = .
c d
− +
Then M11 = d , M12 = c ,
A11 = (−1)1 + 1 det(M11) = d
and A12 = (−1)1 + 2 det(M12) = −c.
a b
So det(A) = = a11A11 + a12A12 = ad − bc.
c d
Examples (Example 2.5.4.2)
−3 −2 4
Let B = 4 3 1 .
0 2 4
3 1 4 1 4 3
Then det(B) = (−3) − (−2) +4
2 4 0 4 0 2
Examples (Example 2.5.4.2)
−3 −2 4
Let B = 4 3 1 .
0 2 4
3 1 4 1 4 3
Then det(B) = (−3) − (−2) +4
2 4 0 4 0 2
Examples (Example 2.5.4.2)
−3 −2 4
Let B = 4 3 1 .
0 2 4
3 1 4 1 4 3
Then det(B) = (−3) − (−2) +4
2 4 0 4 0 2
Examples (Example 2.5.4.2)
−3 −2 4
Let B = 4 3 1 .
0 2 4
3 1 4 1 4 3
Then det(B) = (−3) − (−2) +4
2 4 0 4 0 2
= −3(3 · 4 − 1 · 2) + 2(4 · 4 − 1 · 0) + 4(4 · 2 − 3 · 0)
= 34.
Examples (Example 2.5.4.3)
0 −1 2
0
2 −3 3
−2
Let C = .
0 2 4
0
0 0 2
−1
−3 3 −2 2 3 −2
Then det(C) = 0 2 4 0 − (−1) 0 4 0
0 2 −1 0 2 −1
2 −3 −2 2 −3 3
+2 0 2 0 −0 0 2 4
0 0 −1 0 0 2
Examples (Example 2.5.4.3)
0 −1 2
0
2 −3 3
−2
Let C = .
0 2 4
0
0 0 2
−1
−3 3 −2 2 3 −2
Then det(C) = 0 2 4 0 − (−1) 0 4 0
0 2 −1 0 2 −1
2 −3 −2 2 −3 3
+2 0 2 0 −0 0 2 4
0 0 −1 0 0 2
Examples (Example 2.5.4.3)
0 −1 2
0
2 −3 3
−2
Let C = .
0 2 4
0
0 0 2
−1
−3 3 −2 2 3 −2
Then det(C) = 0 2 4 0 − (−1) 0 4 0
0 2 −1 0 2 −1
2 −3 −2 2 −3 3
+2 0 2 0 −0 0 2 4
0 0 −1 0 0 2
Examples (Example 2.5.4.3)
0 −1 2
0
2 −3 3
−2
Let C = .
0 2 4
0
0 0 2
−1
−3 3 −2 2 3 −2
Then det(C) = 0 2 4 0 − (−1) 0 4 0
0 2 −1 0 2 −1
2 −3 −2 2 −3 3
+2 0 2 0 −0 0 2 4
0 0 −1 0 0 2
Examples (Example 2.5.4.3)
0 −1 2
0
2 −3 3
−2
Let C = .
0 2 4
0
0 0 2
−1
−3 3 −2 2 3 −2
Then det(C) = 0 2 4 0 − (−1) 0 4 0
0 2 −1 0 2 −1
2 −3 −2 2 −3 3
+2 0 2 0 −0 0 2 4
0 0 −1 0 0 2
Examples (Example 2.5.4.3)
2 3 −2 2 −3 −2
det(C) = 0 4 0 + 2 0 2 0
0 2 −1 0 0 −1
4 0 0 0 0 4
= 2 −3 + (−2)
2 −1 0 −1 0 2
2 0 0 0 0 2
+2 2 − (−3) + (−2)
0 −1 0 −1 0 0
= [ 2 · (−4) − 3 · 0 − 2 · 0 ] + 2 [ 2 · (−2) + 3 · 0 − 2 · 0 ]
= −16.
3 × 3 matrices (Remark 2.5.5)
a b c
Let A = d e f .
g h i
Then det(A) = aei + bfg + cdh − ceg − afh − bdi.
The formula in can be easily a b c a b
remembered by using diagram on d e f d e
the right: g h i g h
− − − + + +
Warning: The method shown here cannot be
generalized to higher order.
Geometrical interpretation
(c, d ) (a + c, b + d )
(0, 0) (a, b)
a b
The area of the parallelogram is ad − bc = .
c d
Geometrical interpretation
(g, h, i ) (d + g, e + h, f + i )
(a + d + g, b + e + h, c + f + i )
(a + g, b + h, c + i )
(0, 0, 0)
(d, e, f )
(a, b, c)
(a + d, b + e, c + f )
cofactor expansion
(Since the proof involves some deeper along the j th column
knowledge of determinants, we use this
result without proving it.)
An example (Example 2.5.7)
−3 −2 4
Let B = 4 3 1 .
0 2 4
−2 4 −3 4 −3 −2
Then det(B) = − 4 +3 −1
2 4 0 4 0 2
An example (Example 2.5.7)
−3 −2 4
Let B = 4 3 1 .
0 2 4
−2 4 −3 4 −3 −2
Then det(B) = − 4 +3 −1
2 4 0 4 0 2
An example (Example 2.5.7)
−3 −2 4
Let B = 4 3 1 .
0 2 4
−2 4 −3 4 −3 −2
Then det(B) = − 4 +3 −1
2 4 0 4 0 2
An example (Example 2.5.7)
−3 −2 4
Let B = 4 3 1 .
0 2 4
−2 4 −3 4 −3 −2
Then det(B) = − 4 +3 −1 = 34
2 4 0 4 0 2
An example (Example 2.5.7)
−3 −2 4
Let B = 4 3 1 .
0 2 4
−2 4 −3 4 −3 −2
Then det(B) = − 4 +3 −1 = 34
2 4 0 4 0 2
4 3 −3 −2 −3 −2
=4 −1 +4
0 2 0 2 4 3
An example (Example 2.5.7)
−3 −2 4
Let B = 4 3 1 .
0 2 4
−2 4 −3 4 −3 −2
Then det(B) = − 4 +3 −1 = 34
2 4 0 4 0 2
4 3 −3 −2 −3 −2
=4 −1 +4
0 2 0 2 4 3
An example (Example 2.5.7)
−3 −2 4
Let B = 4 3 1 .
0 2 4
−2 4 −3 4 −3 −2
Then det(B) = − 4 +3 −1 = 34
2 4 0 4 0 2
4 3 −3 −2 −3 −2
=4 −1 +4
0 2 0 2 4 3
An example (Example 2.5.7)
−3 −2 4
Let B = 4 3 1 .
0 2 4
−2 4 −3 4 −3 −2
Then det(B) = − 4 +3 −1 = 34
2 4 0 4 0 2
4 3 −3 −2 −3 −2
=4 −1 +4 = 34.
0 2 0 2 4 3
Triangular matrices (Theorem 2.5.8)
1 0 ··· 0
0 1 ⁞
det(I ) = = 1 · 1 ··· 1 = 1.
⁞ 0
0 ··· 0 1
−2 3.5 2
0 5 −26 = (−2) · 5 · 2 = −10.
0 0 2
−2 0 0
99 0 0 = (−2) · 0 · 2 = 0.
10 −4.5 2
Transposes (Theorem 2.5.10 & Example 2.5.11)
1 0 0 1
1 2 4
4 −2 −1 −3 −3 9
−1 10 4
4 −2 2 4 4 0
1 2 4
0 −2 −2 −1
Elementary row operations (Discussion 2.5.14.1)
a b c a b c
kR2
A= d e f B= kd ke kf
g h i g h i
1 0 0
Let E = 0 k 0 .
0 0 1
Then B = EA.
Since det(E ) = 1 · k · 1 = k,
det(E ) det(A) = k det(A) = det(B) = det(EA).
Elementary row operations (Discussion 2.5.14.2)
a b c a b c
R2 ↔ R3
A= d e f B= g h i
g h i d e f
1 0 0
Let E = 0 0 1 .
0 1 0
Then B = EA.
0 1
Since det(E ) = 1 = 0 · 0 − 1 · 1 = −1,
1 0
det(E ) det(A) = −det(A) = det(B) = det(EA).
Elementary row operations (Discussion 2.5.14.3)
a b c a b c
R3 + kR1
A= d e f B= d e f
g h i g + ka h + kb i + kc
1 0 0
Let E = 0 1 0 .
k 0 1
Then B = EA.
Since det(E ) = 1 · 1 · 1 = 1,
det(E ) det(A) = det(A) = det(B) = det(EA).
Elementary row operations (Theorem 2.5.15)
B1 det(B1) = k det(A)
kRi
A B2 det(B2) = −det(A)
Ri ↔ Rj
Rj + kRi B3 det(B3) = det(A)
After deleting the j th row, the matrices on both sides look exactly the same.
5 0 8 −1
2
R3 + 9 R1 R2 ↔ R3 4R2 0 −2 1 0
A B=
0 0 1 9
1
0 0 0 3
Find det(A).
1
5 · (−2) · 1 · 3 = det(B) = 1 · (−1) · 4 det(A)
10 5
Thus − 3 = −4 det(A) and hence det(A) = 6 .
Elementary column operations (Remark 2.5.18)
Suppose A is singular.
Then (by Remark 2.4.10) B has at least one zero row,
i.e.
* * ··· *
0 * ··· *
B= .
⁞ ⁞
0 ··· 0 0 zero row
Proof:
cR1 cR2 cRn
A ··· cA.
Case 2: A is invertible.
Then (by Theorem 2.4.7) A = E1E2 ··· Ek for some
elementary matrices E1, E2, …, Ek.
Thus
det(AB) = det(E1E2 ··· EkB)
= det(E1) det(E2) ··· det(Ek) det(B)
= det(E1E2 ··· Ek) det(B)
= det(A) det(B).
Invertible matrices (Theorem 2.5.22.3)
−3 −2 4
Let A = 4 3 1 . Note that det(A) = 34.
0 2 4
1
If A is an invertible matrix, then A−1 = det(A) adj(A).
1
Proof: It suffices to show A det(A) adj(A) = I.
1
Then (by Theorem 2.4.12) A−1 = det(A) adj(A).
Let A = (ai j )n × n and A [ adj(A) ] = (bi j )n × n .
As a11 a12 ··· a1n A11 A21 ··· An1
a21 a22 ··· a2n A12 A22 ··· An2
A [ adj(A) ] = ,
⁞ ⁞ ⁞ ⁞ ⁞ ⁞
an1 an2 ··· ann A1n A2n ··· Ann
bi j = ai1Aj1 + ai 2Aj 2 + ··· + ai n Aj n.
Adjoints (Theorem 2.5.25)
A [ adj(A) ] = (bi j )n × n
where bi j = ai1Aj1 + ai 2Aj 2 + ··· + ai n Aj n.
A [ adj(A) ] = (bi j )n × n
where bi j = ai1Aj1 + ai 2Aj 2 + ··· + ai n Aj n.
= det(A) I.
1 1
So det(A)
A [ adj(A) ] = I ⇒ A det(A) adj(A) = I.
Examples (Example 2.5.26.1)
a b
Let A = with ad − bc ≠ 0.
c d
Then M11 = d ,
a b
Let A = with ad − bc ≠ 0.
c d
a b
Let A = with ad − bc ≠ 0.
c d
a b
Let A = with ad − bc ≠ 0.
c d
1 d −b
and A−1 = 1 adj(A) = ad − bc .
det(A) −c a
Examples (Example 2.5.26.2)
1 −1 1
Let B = 0 −1 0 .
1 0 3
T
−1 0
0 3
adj(B) =
Examples (Example 2.5.26.2)
1 −1 1
Let B = 0 −1 0 .
1 0 3
T
−1 0 0 0
−
0 3 1 3
adj(B) =
Examples (Example 2.5.26.2)
1 −1 1
Let B = 0 −1 0 .
1 0 3
T
−1 0 0 0 0 −1
−
0 3 1 3 1 0
adj(B) =
Examples (Example 2.5.26.2)
1 −1 1
Let B = 0 −1 0 .
1 0 3
T
−1 0 0 0 0 −1
−
0 3 1 3 1 0
−1 1
adj(B) = −
0 3
Examples (Example 2.5.26.2)
1 −1 1
Let B = 0 −1 0 .
1 0 3
T
−1 0 0 0 0 −1
−
0 3 1 3 1 0
−1 1 1 1
adj(B) = −
0 3 1 3
Examples (Example 2.5.26.2)
1 −1 1
Let B = 0 −1 0 .
1 0 3
T
−1 0 0 0 0 −1
−
0 3 1 3 1 0
−1 1 1 1 1 −1
adj(B) = − −
0 3 1 3 1 0
Examples (Example 2.5.26.2)
1 −1 1
Let B = 0 −1 0 .
1 0 3
T
−1 0 0 0 0 −1
−
0 3 1 3 1 0
−1 1 1 1 1 −1
adj(B) = − −
0 3 1 3 1 0
−1 1
−1 0
Examples (Example 2.5.26.2)
1 −1 1
Let B = 0 −1 0 .
1 0 3
T
−1 0 0 0 0 −1
−
0 3 1 3 1 0
−1 1 1 1 1 −1
adj(B) = − −
0 3 1 3 1 0
−1 1 1 1
−
−1 0 0 0
Examples (Example 2.5.26.2)
1 −1 1 −3 3 1
1
Let B = 0 −1 0 . B−1 = det(B) 0 2 0 .
−2
1 0 3 1 −1 −1
T
−1 0 0 0 0 −1
−
0 3 1 3 1 0 T
−3 03 11
−1 1 1 1 1 −1
adj(B) = − − = 3
0 22 −10 .
0 3 1 3 1 0
1 0−1−1
−1
−1 1 1 1 1 −1
−
−1 0 0 0 0 −1
Cramer’s Rule (Theorem 2.5.27)
1 1 3 x 0
2 −2 2 y = 4 .
3 9 0 z 3
An example (Example 2.5.28)